2015
DOI: 10.1103/physrevlett.114.055001
|View full text |Cite|
|
Sign up to set email alerts
|

New Steady-State Quiescent High-Confinement Plasma in an Experimental Advanced Superconducting Tokamak

Abstract: A critical challenge facing the basic long-pulse high-confinement operation scenario (H mode) for ITER is to control a magnetohydrodynamic (MHD) instability, known as the edge localized mode (ELM), which leads to cyclical high peak heat and particle fluxes at the plasma facing components. A breakthrough is made in the Experimental Advanced Superconducting Tokamak in achieving a new steady-state H mode without the presence of ELMs for a duration exceeding hundreds of energy confinement times, by using a novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
82
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 29 publications
9
82
1
Order By: Relevance
“…We have concentrated our efforts in the domain where J BS at the edge is large, which tends to coincide with the region where low n = 1 structures dominate (corresponding to the upper half of the graph in figure 8). In our opinion, these structures constitute a very realistic model for the OM observed on JET (Solano 2010) and the EHO detected on DIII-D and other tokamaks (Burrell et al 2005;Suttrop et al 2005;Hu et al 2015). A detailed analysis of the equilibrium state for large edge J BS indicates that a parallel helical current density ribbon forms just outside the q = 3 rational surface with a radial extent that aligns with the vanishing magnetic shear region associated with the flat spot in the q-profile caused by the bootstrap current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have concentrated our efforts in the domain where J BS at the edge is large, which tends to coincide with the region where low n = 1 structures dominate (corresponding to the upper half of the graph in figure 8). In our opinion, these structures constitute a very realistic model for the OM observed on JET (Solano 2010) and the EHO detected on DIII-D and other tokamaks (Burrell et al 2005;Suttrop et al 2005;Hu et al 2015). A detailed analysis of the equilibrium state for large edge J BS indicates that a parallel helical current density ribbon forms just outside the q = 3 rational surface with a radial extent that aligns with the vanishing magnetic shear region associated with the flat spot in the q-profile caused by the bootstrap current.…”
Section: Discussionmentioning
confidence: 99%
“…We interpret these deformations as indicative of the development of an external kink/peeling mode that saturates at finite amplitude. The distortions observed are symptomatic of the edge harmonic oscillation (EHO) (Burrell et al 2005) first reported on DIII-D, but subsequently observed on many other machines (Suttrop et al 2005;Hu et al 2015), and the outer mode (OM) measured on JET (Solano et al 2010). The shape of the last closed magnetic flux surface on TCV at four different cross-sections projected onto a single toroidal plane for β N = 1, 1.49, 1.99 and 2.47 are presented in figure 4.…”
Section: -D Equilibrium Numerical Simulations: Nonlinearly Stable Stmentioning
confidence: 99%
“…Finally, a scenario was developed on EAST [49] which seems to be a combination of the above two scenarios. When lithium is injected into a discharge, an pre-existing edge coherent mode (ECM), thought to be a TEM, is further excited and results in a stable ELM-free scenario.…”
Section: Low-z Impurity Injectionmentioning
confidence: 99%
“…As another Li wall conditioning method, the real-time Li aerosol injection technique is also developed on EAST and actively supports the achievement of long-pulse ELMfree H modes [26,27]. The edge impurity levels and particle recycling can be reduced by real-time Li injection, thus improving plasma performances.…”
Section: Control Of W Sputtering Sourcementioning
confidence: 99%